TAFSIR AYAT-AYAT KAUNIYAH: Studi Komparasi Pemikiran Dr. Zakir Naik dan Dr. Maurice Bucaille - M. Rifaki; Luthfi Raziq; Abdul Azis (Jurnal Studi Qur'an dan Tafsir, 2024)
An assumption, that al-Quran is in accord with every era and place, has been proven by some researchers, thinkers, and interpreters, acknowledging that the al-Quran is in accordance with the development of modern knowledge/science. Loads of discovered findings lately have been written in al-Quran 14 centuries ago. Among those researchers, thinkers, and interpreters are Dr. Zakir Naik and Dr. Maurice Bucaille, proving it through their research and interpreting results on al-Quran and science. This research is meant to dig three things up: first, how is the interpretation of both mentioned researchers concerning kauniyah verses? Second, how suitable are their interpretations for the al-Quran interpreting principles? This research uses a comparative method, analyzing the foremost works of both researchers: “The Bible, The Qur’an, and Science” by Dr. Maurice Bucaille and several speeches as well as the scientific writings made by Dr. Zakir Naik. The used theoretical approach is scientific interpretation theory, analyzing how kauniyah verses are interpreted in modern science framework. The research findings aver that Dr. Maurice Bucaile emphasizes the scientific validity of al-Quran by drawing attention to the verses fitting the modern findings in biology and genetics; besides, Dr. Zakir Naik shows apologetic aspects in maintaining al-Quran righteousness through his scientific debate with non-Moslem view. It could be understood, in both interpretations of analyzing kauniyah verses, that the method and the principles they use are mostly according to the principles by the former ulama of exegesis, despite that there are some they don’t use; however, still, it can be said that both researchers are in the way how an interpreter should be.